Ghettostadt : Lódz and the making of a Nazi city - Horwitz, Gordon J. 1953- (Belknap Press of Harvard Univ. Press, 2008)
Under the Third Reich, Nazi Germany undertook an unprecedented effort to refashion the city of Lodz. Home to prewar Poland's second most populous Jewish community, this was to become a German city of enchantment--a modern, clean, and orderly showcase of urban planning and the arts. Central to the undertaking, however, was a crime of unparalleled dimension: the ghettoization, exploitation, and ultimate annihilation of the city's entire Jewish population. This book is an examination of the Jewish ghetto's place in the Nazi worldview. Exploring ghetto life in its broadest context, it maneuvers between the perspectives and actions of Lodz's beleaguered Jewish community, the Germans who oversaw and administered the ghetto's affairs, and the "ordinary" inhabitants of the once Polish city, showing how the Nazis exploited Jewish institutional traditions, social divisions, faith in rationality, and hope for survival to achieve their wider goal of Jewish elimination.--From publisher description.